IDENTIFIKASI JAMUR Aspergillus sp PADA ROTI TAWAR SEBELUM MASA KADALUARSA DI PASAR BURUNGTUNGKU KOTA BANDUNG - Ni'matul - Murtafi'ah (Klinikal Sains : Jurnal Analis Kesehatan, 2021)
Bread is a food made from wheat flour fermented with yeast (Saccharomyces cerevisiae) and the addition of other ingredients. Fungi are the main microorganisms that play an important role in the process of making and spoiling bread. Aspergillus sp is a common contaminant fungus on various substrates, one of which is white bread The purpose of this study was to identify the fungus Aspergillus sp in white bread before the expiration date at the Pasar Minggu Burung Tungku, Bandung City.The study was conducted using a descriptive method, namely by isolating the fungus on SDA media (Sabaroud Dextrose Agar) then stored for 5 days in an incubator at 27oC, after that it was examined under a microscope with the addition of LPCB (Lactophenol Cotton Blue) solution.Based on observations from 4 types of white bread, 3 types of white bread 2 days before the expiration date, the positive results were found to be contaminant fungi in samples of white bread 1, 3, and white bread 4. In samples of white bread 1 and 3 found contaminant fungi Aspergillus fumigatus and in sample of white bread 4 found contaminant fungi Aspergillus flavus.From the results of the research above, it can be concluded that the white bread 2 days before the expiration date was contaminated by Ascomycetes fungi, namely Aspergillus sp. Keywords: Bread, Aspergillus sp, Aspergillus flavus, Aspergillus fumigatus.